SHRIMP CULTURE OF Penaeus monodon WITH ZERO WATER EXCHANGE MODEL (ZWEM) USING MOLASSES - Pohan Panjaitan (JOURNAL OF COASTAL DEVELOPMENT, 2010)
One of the main obstacles to develop an intensive aquaculture is the accumulation of toxic inorganic nitrogenwhich should be kept very low by frequent water exchange or recycling of the water through a biofilter.This study describes another method of removing inorganic nitrogen using heterotrophic bacteria populationof which was augmented by the addition of a carbonaceous substance, molasses, to increase the feed C:Nratio under laboratory condition. The principal aim of study was to establish correlation C:N ratio levelwith levels of ammonia, nitrite, dissolved oxygen, pH and shrimp growth in Penaeus monodon shrimpculture with Zero Water Exchange Model (ZWEM) using molasses as carbon resource. It was found thataddition of molasses to shrimp farming with ZWEM had a role in removing ammonia and nitrite. Also,application of molasses to laboratory tanks increased the growth and percentage weight gain of shrimps andincreased the population of heterotrophic bacteria.